Impact of geochemical and geomechanical changes on CO2 sequestration potential in sandstone and limestone aquifers - Raza, A.; Gholami, Raoof; Rabiei, M.; Rasouli, V.; Rezaee, Reza; Fakhari, Nikoo (WILEY PERIODICALS, INC, 2019)
CO2 storage in different geological formations has been recognized as one of the promising mitigation approaches to reduce the emission of CO2 into the atmosphere. There are many complex hydro-chemo-mechanical interactions (effective stress changes, water acidification, and mineral dissolution) that may take place in a storage site during or after injection, reducing the integrity of formations in the short or long term. Although there have been several studies carried out in the past to assess the feasibility of sandstones and limestone formations as a safe CO2 storage site, the effect of hydrological, mechanical, and chemical processes on the storage site integrity has not been deeply addressed. The aim of this study is to couple thermo-hydro-chemo-mechanical processes upon CO2 injection and assess their impact on the key storage aspects of quartz-rich sandstone and calcite-rich limestone. A numerical model was built to simulate CO2 flooding into a saline aquifer with sandstone and limestone composition for 500 years. The results obtained indicated that geochemical activity and CO2 dissolution are significantly higher in limestone and may increase the porosity by ∼16%. During injection, a decrease in the reservoir strength was observed in both rock types upon exposure to CO2. A remarkable variation in the geomechanical characteristics was also revealed in the sandstone after injection. However, ground displacements (subsidence) of 0.0017 and 0.033 m were, respectively, observed in sandstone and limestone aquifers, at the end of 500 years. It is recommended to consider a high-strength reservoir for carbon capture and storage (CCS) projects in order to reduce the likelihood of compaction. It was also found that both rock types have a good storage capacity, injectivity, and trapping potentials (the structural and dissolution trappings) to capture and hold CO2 in place. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.